ANALISIS KESULITAN BELAJAR SISWA DALAM PEMBELAJARAN MATEMATIKA PADA MATERI PERKALIAN DI KELAS III SD NEGERI 40 PALEMBANG - Berliana Anggraeni; M. Juliansyah Putra; Farhan Yadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to identify and understand students' learning difficulties in learning mathematics in multiplication material at SD Negeri 40 Palembang. The method used in this research is descriptive qualitative, which aims to provide an in-depth description of the phenomenon being studied. Data collection techniques in this research include direct observation, in-depth interviews with students and teachers, as well as documentation of various learning materials and other relevant records. Data analysis was carried out through the stages of data collection, data reduction, data presentation, and drawing conclusions. The results of the research show that difficulties in learning mathematics in multiplication material at SD Negeri 40 Palembang are caused by various factors which can be recommended as internal and external factors. Internal factors of learning difficulties include students' low interest in mathematics, low strong learning motivation, and students' inability to understand and focus during the learning process. Meanwhile, external factors that influence learning difficulties are a lack of variation in the teaching media used by teachers, the influence of a family environment that does not support student learning activities, and a social environment with school friends that is not conducive.